Microbial Evaluation of Neutropenic Diet in Bone Marrow Transplant Department in Iran - Mahsa Tousi; Abdolreza Norouzy; Mohammad Vaezi; Ali Ghasemi; maryam khosravi; Ardeshir Ghavamzade (Journal of Fasting and Health, 2018)
Background: The use of a neutropenic diet after hematopoietic stem cell transplantation (HSCT) was instituted more than 30 years ago. This diet was targeted toward preventing from infection with organisms colonizing the gastrointestinal tract and the food-borne pathogens, which are the most important cause of illness and death in developing countries. Regarding this, the present study aimed to evaluate neutropenic diet in patients undergoing bone marrow transplantation in a selected hospital. This study also sought to investigate the role of hospital foods in the transmission of clinically important bacteria to the hospitalized patients. Materials and Methods: This cross-sectional study was conducted on the specimens of the foods served in the Bone Marrow Transplant Department of Shariati Hospital, Tehran, Iran. The samples were evaluated in terms of bacterial contamination using the standard method ‎of American Public Health Association and Food and Drug Administration (FDA). Results: According to total bacteria and coliform counts, No contamination was detected in any of the tested specimens. Conclusion: As the findings indicated, the neutropenic diet, was found to be fully in line with the standards of the Ministry of Health and FDA both in terms of guidelines and food analysis.